Future engineers' perception of basic professional competence and their ability to innovative thinking - Kuznetsova, Hanna (Institutul Internațional de Management Imi-Nova, 2023)
Martial law in Ukraine contributes to rethinking and changing directions of work in the economy and in education. New innovative approaches and specialists are needed to rebuild the country's infrastructure, who are able to think innovatively and creatively. Determination of features of future engineers' perception of basic professional competence and their ability to innovative thinking was carried out using a survey among undergraduate engineering majors of the first year of study of the Kharkiv National University of Urban Economy named after O. M. Beketova. Taking into account the results of the survey, during the martial law, the age structure of those seeking education changed: the number of older students increased; it is also observed that future engineers underestimate such an important professional quality as the ability to apply knowledge from technical disciplines; higher education applicants do not consider the ability to self-study important. As a result, this important personal quality is regarded as one that has almost no influence on the development of innovative thinking. The study points to the need to improve and develop the technical training of future specialists, their ability to self-study and creative thinking.
Keywords: future engineers; basic professional competence; innovation; innovative thinking